COMPETENCY CRITERIA: ESSENCE AND IMPORTANT ASPECTS (Universal International Scientific Journal, 2026)
This article discusses the essence, main features, and assessment methods of competency criteria. It explains how competency criteria are used to assess personal, professional, and communicative leadership competencies.
Keywords: competence, competence criteria, professional skills, development, assessment.